The psychology of crime, policing and courts - Kapardēs, Andreas; Farrington, David (Routledge studies in criminal behaviour, 2016)
Foreword / Ray Bull -- Introduction: psychology, crime, policing and courts / Andreas Kapardis and David P. Farrington -- Crime and antisocial behaviour -- The concentration of convictions in two generations of families / David P. Farrington and Rebecca V. Crago -- Self-reported juvenile delinquency in three surveys over 38 years : a german study on the crime drop / Friedrich Lösel, Doris Bender, Zara Sünkel and Mark Stemmler -- What factors protect adolescent bullies from developing into criminal and violent offenders? / Maria M. Ttofi and David P. Farrington -- Cyberbullying : does parental online supervision and youngsters' willingness to report to an adult reduce the risk? / Anna C. Baldry, Anna Sorrentino and David P. Farrington -- Violence risk : the actuarial illusion / David J. Cooke -- The psychopath : continuity or change? : stability of psychopathic traits and predictors of stability / Henriette Bergstrøm, Adelle E. Forth and David P. Farrington -- Policing and detecting deception -- Questioning the interrogational practices of u.s. law-enforcement officers : legal and psychological perspectives / David Walsh, Sean O'Callaghan and Rebecca Milne -- Police interviews of sexually abused children : the state of the art in differentiating truthful and false accounts / Marilena Kyriakidou -- Psychophysiological detection of deception : a review of detection methods, recent research and potential forensic applications / Gershon Ben-Shakhar -- Courts and sentencing -- Wrongful convictions : psychological and criminal justice system contributors / C. Ronald Huff -- The English jury : issues, concerns and future directions / Nicola Padfield -- Extra-legal factors that impact on sentencing decisions / Andreas Kapardis -- Reflections on sentencing in England and Wales / Nicola Padfield